2011
DOI: 10.1007/s12975-011-0082-4
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hypothermia Suppresses Calcium-Sensing Receptor (CaSR) Induction Following Forebrain Ischemia While Increasing GABA-B Receptor 1 (GABA-B-R1) Expression

Abstract: Hypothermia improves neurological outcome from cardiac arrest. The mechanisms of protection are multifold, but identifying some may be useful in exploring potential therapeutic targets. The extracellular calcium-sensing receptor (CaSR) was originally found in parathyroid cells in which the receptor senses minute changes in extracellular [Ca2+] and promotes Ca2+ influx and intracellular Ca2+ release. The CaSR is broadly expressed in the CNS and colocalized with the inhibitory γ-aminobutyric acid-B receptor 1 (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 35 publications
2
50
0
1
Order By: Relevance
“…We and others have shown that intraischemic and postischemic hypothermia can be neuroprotective partially by inhibiting the acute inflammatory response (Toyoda et al, 1996;Maier et al, 1998;Han et al, 2002;Deng et al, 2003;Kim et al, 2011). Nevertheless, the mechanisms underlying this protective effect are still not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that intraischemic and postischemic hypothermia can be neuroprotective partially by inhibiting the acute inflammatory response (Toyoda et al, 1996;Maier et al, 1998;Han et al, 2002;Deng et al, 2003;Kim et al, 2011). Nevertheless, the mechanisms underlying this protective effect are still not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo models of ischemia demonstrated a loss of GABA B receptors 1-4 days after the insult (7)(8)(9). Because considerable ischemia-induced neuronal death occurs during this time period, the loss of GABA B receptors might be due, at least in part, to a loss of GABA B receptorexpressing neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased GABAergic activity appears to contribute to neuronal overexcitation (6), and there are indications that GABA B receptors are down-regulated under ischemic conditions (7)(8)(9)(10). This suggests that impaired GABA B receptor signaling contributes to excitotoxicity.…”
mentioning
confidence: 99%
“…The possible mechanisms of therapeutic hypothermia for neuroprotection include: 1) Therapeutic hypothermia can inhibit the biosynthesis, release and uptake of several catecholamines and neurotransmitters especially glutamate and dopamine leading to brain damage; [16][17][18][19][20][21] 2) It can preserve the blood brain barrier and adenosine triphosphate stores, restitute cerebral microcirculation after ischemia, decrease intracranial pressure and increase cerebral brain blood flow; [22][23][24][25] 3) It also can reduce the amount of cell death in certain brain regions. [26][27][28][29][30] Although therapeutic mild hypothermia benefits CA patients, adverse events caused by mild hypothermia should not be neglected. Adverse events reported in all trials included pneumonia, pulmonary edema, bleeding, need for platelet transfusions, sepsis, arrhythmia, recurrence of CA, renal failure or oliguria, hemodialysis, pancreatitis, and seizures.…”
Section: Discussionmentioning
confidence: 99%